2016
DOI: 10.7196/sajcc.2016.v32i2.275
|View full text |Cite
|
Sign up to set email alerts
|

The capabilities and scope-of-practice requirements of advanced life support practitioners undertaking critical care transfers: A Delphi study

Abstract: Background. Critical care transfers (CCT) refer to the high level of care given during transport (via ambulance, helicopter or fixed-wing aircraft) of patients who are of high acuity. In South Africa (SA), advanced life support (ALS) paramedics undertake CCTs. The scope of ALS in SA has no extended protocol regarding procedures or medications in terms of dealing with these CCTs. Aim. The aim of this study was to obtain the opinions of several experts in fields pertaining to critical care and transport and to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The exact format of such a qualification, however, is yet to be determined. A previous study [18] has also suggested that an additional scope of practice is required to support the CCT of a neonate, and this suggestion is in line with the patient demographic and attachment and medication requirements of the patients described in this study.…”
Section: Researchsupporting
confidence: 85%
“…The exact format of such a qualification, however, is yet to be determined. A previous study [18] has also suggested that an additional scope of practice is required to support the CCT of a neonate, and this suggestion is in line with the patient demographic and attachment and medication requirements of the patients described in this study.…”
Section: Researchsupporting
confidence: 85%
“…The lack of a contextually relevant and universally accepted definition of a CCT results in a lack of standardisation of local CCT practices and support for the ambulance crews. [7,8] There seems to be ongoing confusion and debate as to whether the patient requiring transfer indeed warrants a CCT team, and if the team has the required qualifications, competencies, equipment and experience for the transfer. Internationally, CCT is usually reserved for high-acuity patients transferred between ICUs and is performed by specialist CCT teams.…”
Section: Discussionmentioning
confidence: 99%
“…In SA, CCTs of high-acuity patients are commonly conducted by advanced life support (ALS) providers. [7] The professional registering body in SA, the Health Professions Council of South Africa (HPCSA), further distinguishes between different ALS providers, allowing for registration on one of two registers (paramedic and emergency care practitioner (ECP)). Therefore, to perform CCTs, an ALS provider can either be qualified as a paramedic or an ECP.…”
Section: Research Participantsmentioning
confidence: 99%
See 2 more Smart Citations